PENGARUH TERAPI RELAKSASI BENSON TERHADAP TEKANAN DARAH LANJUT USIA (LANSIA) DENGAN HIPERTENSI PENGARUH TERAPI RELAKSASI BENSON TERHADAP TEKANAN DARAH LANJUT USIA (LANSIA) DENGAN HIPERTENSI - royani; Sondang Deri Maulina Pasaribu; Gugun gugun (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction: At old age there will be various setbacks in the organs of the body, therefore the elderly are very susceptible to diseases such as hypertension. The incidence of hypertension worldwide reaches more than 1.3 billion people, which figure represents 31 percent of the adult population in the world, which has increased by 5.1 percent. Hypertension is one of the most dangerous health problems around the world because hypertension is a major risk factor that affects cardiovascular diseases such as heart attack, heart failure, stroke and kidney disease in which ischemic heart disease and stroke are the two main causes of death in the world. The research objective: to determine the effect of Benson relaxation therapy on blood pressure in elderly people with hypertension at Rt 004 Rw 01 Parung Serab Ciledug, Tangerang city. Research method: using. This type of quantitative research design is Pre Experimental design with the One Group Pretest Posttest method. The population is the elderly who live in parung serab RT 004, which number 30 elderly. The sampling technique used Quota sampling with a sample size of 23 respondents. The statistical test used is Wilcoxon. The results of the study: 23 respondents showed Systolic Blood Pressure before Benson Relaxation was 159.00 and after Benson Relaxation was 135.87, it meant a decrease of 23.13. Diastolic blood pressure before Benson Relaxation is 95.52 and after Benson Relaxation is 79.91 it means that it has decreased by 15.61. The results of the analysis show that the results of the Wilcoxon test for differences in systolic and diastolic blood pressure obtained p-value (0.000) <0.05. Conclusion: based on the test results, it is concluded that there is an effect of Benson Relaxation on Blood Pressure Reduction in the elderly (Elderly).